Representation of Hedonism by the Characters in Gossip Girl Series 2021 - Adi, Ni Putu Khetrina; Matradewi, Ni Ketut Widhiarcani; Soethama, Putu Lirishati (Humanis, 2022)
This study aimed to identify the types of hedonism and analyze the effects of hedonism on the characters in the Gossip Girl series. In analyzing the type of hedonism this study used the theory type of hedonism proposed by Weijers (2012). This study also used the theory effect of hedonism by Veenhoven (2003) based on the social groups presented in the series. The data were taken from the series entitled the Gossip Girl. The documentation method and note-taking technique were applied in collecting the data. In analyzing the data this study used a descriptive qualitative approach. The findings show that the character in the Gossip girl Series represents two types of hedonism namely folk hedonism and hedonistic egoism/selfish hedonism. The second finding is hedonism has an effect on the lives of characters namely reducing happiness, disrupting their physical and mental health, being treated arbitrarily.